Synthesis of Cellular Silica Using Microbubbles as Templates - Zirui Zhao; Jiamei Liu; Xifeng Xi; Yulong Wu; Junshe Zhang (Nanomaterials, 2022)
In this work, cellular silica was synthesized by using microbubbles as templates, which contain a mixture of argon and silicon tetrafluoride (SiF4). The latter is generated from decomposition of hexafluorosilicic acid (H2SiF6) at ambient conditions. The specific surface area of cellular silica can be as high as 130 m2/g, the size of the cavity is hundreds-of-nanometers, and the thickness of the cavity wall is around 30 nm. The cavity size, apparent packing density, and porosity of cellular silica strongly depend on the nature of the aqueous solutions; the cavity size appears to be negatively proportional to the surface tension, but thickness of cavity walls seems to be weakly affected by the aqueous properties. An attempt was made to introduce aluminum atoms in situ in the second-coordination sphere of Si atoms and/or load aluminum into the silica structure. Cellular silica with large pores facilitate the transfer of large molecules, including polymers and enzymes; thus, it could find applications in (bio)catalysis, sorption, controlled release and separations.